Communication 2 Braumann II EMMBM - Braumann, Carlos A. (2008)
Scientific meeting: II Encontro em Modelagem Matemática em Bio-Medicina, Campinas, Brazil, Feb 1-2, 2007. Invited conference on stochastic differential equation and finantial applications.